Marketing Strategy Analysis of Nano Tea Product Based on Mangosteen Peel (Gracinia Mangostana) to Promote Functional Foods Industry - Syukri Yusuf Nasution; Gita Andini; Yoga Prawira; Dhini Azzahra (School of Business, IPB University (SB-IPB), 2019)
A marketing strategy analysis is an overview of the potential that can be generated from marketing aspects. This analysis is conducted to overview the feasibility of the product if it entered the market. In this research, the marketing strategy analysis uses three methods: (1) Business Model Canvas (BMC) analysis as a business model of the product; (2) Competitor Intelligence (CI) analysis to observe the product’s position to be developed, compared to the existing products in the market; and (3) Marketing Element analysis to analyze the potential market of the product which can be observed from segmentation, market size potential market, and also the size of the market share of the product. This study uses qualitative and quantitative methods by collecting both secondary and primary data. In the Business Model Canvas (BMC) analysis shows the nano tea product based on mangosteen peel has two business models that are being recommended for the marketing strategy, those are Business to Business (B2B) and Business to Customer (B2C) models. In the Competitor Intelligence (CI) analysis, shows that the product has two success factors to increase the competitive value of the product i.e. success factors in the form of tea powder and nano-size. Those factors will make the product has better efficacy and functions compared to similar tea in other form. While the results of marketing elements analysis of the product will be focused on West Java market, with the value of market share of 0.05% or about 35,904 ton/years from the total market of 72.903,6 tons/years.Keywords: market strategy, competitor intelligence, business model canvas, marketing analysis